The Brazilian woman: from the colonial photography to contemporary Portuguese photography - Travassos, Lorena (2017)
This study aims to carry out an initial analysis of how the Brazilian woman image is shaped by a discourse that is historically constructed and reinforced by colonial photography. This visuality has endured through the ages and represents a form of contemporary colonialism, as it is characterized by an identity reductionism disguised as a global ideology. The possibility of paradox prevalence in these speeches is analyzed through a critical view of the work of André Cepeda and Miguel Valle de Figueiredo, Portuguese photographers who has produced photography artwork about the Brazilian woman. In these images, the construction of a visual concept of Brazilian women revealed underlying statements supported by their perceptions and experiences, as well as in generalized beliefs. Thus, it was concluded that the understanding of the image of Brazilian women as portrayed by those photographers shows itself covered of brand new colonizing processes in which the Brazilian woman’s image is linked with a sense of an available and sensual body, imbued with the concept of a colonial body that still persists in contemporary imagery.